Three-site co-doped lithium titanate carbon coated material as well as preparation method and application thereof
By adopting three-site co-doping method in lithium titanate materials, potassium, aluminum, and fluorine plasma are introduced to improve the electronic conductivity and lithium ion diffusion rate of the material, and the low conductivity and poor rate performance of lithium titanate materials are solved. The problem has significantly improved the electrochemical performance and safety performance of lithium-ion batteries.
Patent Information
- Application Number
- CN202411536978.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-02-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Lithium titanate material has limited its further development in lithium-ion batteries due to its low intrinsic conductivity, limited lithium storage capacity and poor rate performance.
Through the three-site co-doping method, lithium neodymium acid material is combined with carbon material and co-doped with potassium, aluminum, and fluorine plasma to improve the electronic conductivity and lithium ion diffusion rate of the material.
The electronic conductivity and cyclic stability of lithium titanate materials have been significantly improved, and the electrochemical performance and safety performance of lithium-ion batteries have been enhanced.
Smart Images

Figure CN119481027A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of organic lithium ion battery electrode materials, and specifically relates to a three-site co-doped lithium titanate carbon coating material and a preparation method and application thereof. Background Art
[0002] Lithium-ion batteries (LIBs) are widely used in electronic devices, power vehicles, and energy storage power stations due to their advantages such as high operating voltage, light weight, and high power density. The negative electrode material of lithium-ion batteries is one of the key factors restricting the capacity of lithium-ion batteries. Since the invention of lithium-ion batteries, the negative electrode materials of lithium-ion batteries have been replaced several times, including carbon materials, silicon-based materials, tin-based materials, alloy materials, and metal oxide materials. Today, lithium-intercalated carbon negative electrode materials can be commercially produced. This is because the cycle and safety of graphite materials have been greatly developed and improved, but there are still many disadvantages: the first charge and discharge capacity is generally very low, the synthesis route is relatively complicated, and dendrites are prone to cause safety problems. In comparison, alloy materials can obtain more specific capacity due to different lithium de- / intercalation methods, but the volume shrinkage of the material when lithium ions are inserted / extracted will cause the material to become powder, which limits the commercial development of the material. Compared with other negative electrode materials, lithium titanate (Li4Ti5O 12 ) has been studied by many energy workers because of its "zero strain" advantage. "Zero strain" means that the volume and lattice constant of lithium titanate materials change very little (≤0.2%) during the phase change process, the theoretical specific capacity is 175mAh / g, and it has a high and stable charging platform of about 1.55V (vs.Li / Li + ), the higher charge and discharge platform makes lithium titanate not produce lithium dendrites, which can effectively prevent lithium dendrites from piercing the diaphragm and causing short circuit, significantly improving the safety performance of lithium-ion batteries. At the same time, due to the higher charge and discharge platform, the process of lithium insertion and extraction does not generate SEI film, making its cycle stability and coulomb efficiency higher, making it an ideal negative electrode alternative material for the new generation of lithium batteries. However, lithium titanate has a high intrinsic conductivity and Li + The low diffusion coefficient limits its further development. Summary of the invention
[0003] In order to solve the problems of low electronic conductivity, limited lithium storage capacity and poor rate performance inherent in lithium titanate materials, the main purpose of the present invention is to provide a three-site co-doped lithium titanate carbon-coated material, in which the lithium titanate material is composited with the carbon material, and the lithium, titanium and oxygen sites in the lithium titanate material are replaced by co-doping with trace amounts of potassium, aluminum and fluorine, so as to effectively improve the electronic conductivity of the material surface, and the synergistic effect between the doped anions and cations can induce improvement of the internal properties of the material, thereby improving the cycle stability of the lithium titanate material in an organic lithium ion battery.
[0004] Another object of the present invention is to provide a method for preparing a three-site co-doped lithium titanate carbon-coated material, which has a simple process and is suitable for large-scale production.
[0005] Another object of the present invention is to provide a three-site co-doped lithium titanate carbon coating material for use in an organic lithium ion battery.
[0006] To achieve the above object, the present invention adopts the following technical solution:
[0007] The present invention provides a three-site co-doped lithium titanate carbon coating material, comprising a carbon coating material, a lithium titanate material, and anions and cations doped in the lithium titanate material; wherein:
[0008] The carbon coating material is selected from one or a combination of two or more of glucose, sucrose, citric acid, tannic acid, and hexadecylamine;
[0009] The cation is selected from one or a combination of two or more of potassium, iron, gadolinium, aluminum, tin, lanthanum, copper, and tin ions;
[0010] The anion is selected from one or a combination of two or more of bromine, chlorine, fluorine, iodine, silicate, carbonate, and sulfate;
[0011] The molar content of the anions and cations is less than 10%.
[0012] Preferably, the cation is potassium and aluminum, replacing lithium and titanium sites respectively; and / or the anion is fluorine, replacing oxygen sites.
[0013] The present invention also provides a method for preparing a three-site co-doped lithium titanate carbon coating material, comprising the following steps:
[0014] The titanium source is dissolved in a solution containing carbon materials, and a lithium source, a doped potassium source, an aluminum source and a silicon source are added, and the solution is heated, stirred, dried, ground and sintered at high temperature in sequence to obtain the product.
[0015] Preferably, the titanium source is selected from one or more of tetrabutyl titanate, titanium isopropoxide, and titanium dioxide, and more preferably tetrabutyl titanate.
[0016] Preferably, the carbon material is selected from one or more of glucose, sucrose, citric acid, tannic acid, and hexadecylamine, more preferably hexadecylamine.
[0017] Preferably, the solvent used in the solution of the carbonaceous material is selected from one or more of deionized water, ethanol, n-propanol, isopropanol, ethylene glycol, and propylene glycol, more preferably ethanol.
[0018] Preferably, the lithium source is selected from one or more of lithium carbonate, lithium hydroxide monohydrate, lithium nitrate or lithium acetate, more preferably lithium acetate.
[0019] Preferably, the potassium source is selected from one or more of potassium acetate, potassium chloride, potassium sulfate, potassium nitrate and potassium dihydrogen phosphate, more preferably potassium acetate.
[0020] Preferably, the aluminum source is selected from one or more of aluminum sulfate, aluminum chloride, aluminum nitrate, aluminum acetate, and aluminum carbonate, more preferably aluminum acetate.
[0021] Preferably, the fluorine source is selected from one or more of hydrogen fluoride, hydrofluoric acid, fluorspar, sodium fluoride, potassium fluoride, aluminum fluoride, and sulfur hexafluoride, more preferably hydrogen fluoride.
[0022] Preferably, the mixture is heated and stirred in an oil bath at a temperature of 60 to 150° C. for a heating time of 8 to 50 h; more preferably, the heating temperature is 80° C. for a heating time of 24 h.
[0023] Preferably, the drying time is 2 to 24 hours, preferably 24 hours.
[0024] Preferably, the grinding time is 2 to 120 min, preferably 30 min.
[0025] Preferably, the sintering temperature is 400-800°C, the sintering time is 2-12h, and the sintering heating rate is 1-6°C / min; more preferably, the sintering temperature is 700°C, the sintering time is 10h, and the sintering heating rate is 3°C / min.
[0026] The present invention also provides an electrode, comprising the three-site co-doped lithium titanate carbon coating material.
[0027] The present invention also provides the use of the three-site co-doped lithium titanate carbon coating material or the electrode in an organic lithium ion battery.
[0028] Compared with the prior art, the present invention proposes a three-site co-doped lithium titanate carbon-coated material, which effectively expands the unit cell size of the material and provides a larger lithium ion transmission channel through the coordinated doping between potassium and aluminum ions; doping with fluorine ions can reduce the charge transfer resistance of the lithium titanate / electrolyte interface and increase the lithium ion diffusion rate, thereby improving the electrochemical performance; after the lithium titanate material is composited with the carbon material, it can effectively inhibit particle agglomeration, increase the material specific surface area, and improve the conductivity of the material surface. The beneficial effects of the present invention are:
[0029] 1. By combining surface modification with lattice doping, the electronic conductivity of lithium titanate materials is greatly improved. The resulting material exhibits excellent electrochemical properties and can be used as the negative electrode material of lithium-ion batteries. It has high safety and wide application, and can be applied to energy storage equipment, backup power supply, reserve power supply, etc.
[0030] 2. The present invention adopts the sol-gel method to prepare three-site co-doped lithium titanate carbon-coated materials. The steps are simple, no complicated process flow is required, the cost is low, there is no pollution, it is easy to industrialize, the required raw materials are abundant and cheap, and the production cost is low. It is a green, environmentally friendly and efficient preparation method. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 This is the SEM image of the lithium titanate carbon-coated material synthesized in Example 1.
[0032] Figure 2 This is the cycle curve of the button battery prepared in Example 2. Specific embodiments
[0033] The embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Other embodiments obtained by those skilled in the art without any creative work are all within the scope of protection of this patent.
[0034] In order to describe the present invention more clearly, an electrode material, a preparation method and an application provided by the present invention are described in detail below in conjunction with embodiments.
[0035] Example 1
[0036] 70 mL of anhydrous ethanol was measured, and 0.46 g of hexadecylamine (HDA) was added and stirred continuously until the solid was completely dissolved. Then, 1.58 mL of titanium isopropoxide liquid was added dropwise, and after stirring for 1 h, lithium acetate, potassium acetate, aluminum acetate, and hydrogen fluoride were added according to the stoichiometric ratio. After stirring for 6 h, the mixture was placed in a 100 ° C oil bath and stirred for evaporation to obtain a lithium titanate precursor. Under the protection of high-purity argon, the mixture was pre-sintered at 450 ° C for 4 h, and then sintered at 700 ° C for 8 h to obtain undoped Li4Ti5O 12 / C materials and doped Li 3.97 K 0.03 Ti 4.95 Al 0.0 5O 11.95 F 0.05 / C material.
[0037] Figure 1 For Li 3.97 K 0.03 Ti 4.95 Al 0.05 O 11.95 F 0.05 / C material SEM image, the minimum particle size of the material is about 150nm.
[0038] Example 2
[0039] The lithium titanate carbon-coated material before and after doping prepared in Example 1, conductive black (Super P), and binder (PVDF) were mixed uniformly in a mass ratio of 7:2:1, and then the solvent N-methylpyrrolidone (NMP) was added to grind into slurry, coated on copper foil with a thickness of 200 μm, and placed in a vacuum oven at 80°C for 12 h to obtain an electrode sheet.
[0040] The electrode sheets prepared above were cut into φ12 mm discs, φ14 mm lithium sheets were used as negative electrodes, glass fiber was used as separators, 1M LiPF6 (EC:DMC:DEC=1:1:1 Vol%) was used as electrolyte, button cells were assembled in an argon-filled glove box, and electrochemical performance tests were carried out at 1.5-2.5 V using a LAND test system.
[0041] Figure 2 For the button cell above, the current density is 3000 mAg -1 The comparison of the cycle curves of 3000 cycles under the condition of , shows that the initial specific capacity of the first cycle of doped lithium titanate is 114.2 mAh g -1 After 3000 cycles, the capacity is still 105.62 mAh g -1 The capacity retention rate is 92.27%. The initial specific capacity of lithium titanate before doping is only 88 mAh g -1 , the capacity retention rate is 74.58% after 3000 cycles.
[0042] The difference between Examples 3 to 7 and Examples 1 and 2 is that the ratio of doping elements K, Al, and F = x:y:z (molar ratio). -1 The charge and discharge performance at current density is shown in Table 1.
[0043] Table 1
[0044]
[0045] It can be seen from Table 1 that when the doping elements K, Al, and F are 0.1:0.1:0.05 (molar ratio), the prepared electrode sheet has a relatively higher specific capacity when used in organic lithium-ion batteries, and the first-cycle coulomb efficiency is also relatively high.
[0046] The difference between Examples 8 to 12 and Examples 1 and 2 is that the sintering temperatures are different. The specific properties are shown in Table 2.
[0047] Table 2
[0048]
[0049]
[0050] As shown in Table 2, when the sintering temperature is too high, the material is easy to agglomerate; when the sintering temperature is too low, the material has low crystallinity; when the sintering temperature is 700°C, its specific capacity is the highest, the first-cycle coulombic efficiency is the highest, and the cycle performance is more stable.
[0051] The above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit the protection scope of the present invention. Although the present invention is described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention can be modified or replaced by equivalents without departing from the protection scope of the present invention.
Claims
1. A three-site co-doped lithium titanate carbon coating material, characterized in that: It includes carbon coating material, lithium titanate material and anions and cations doped in the lithium titanate material; wherein: The carbon coating material is selected from one or a combination of two or more of glucose, sucrose, citric acid, tannic acid, and hexadecylamine; The cation is selected from one or a combination of two or more of potassium, iron, gadolinium, aluminum, tin, lanthanum, copper, and tin ions; The anion is selected from one or a combination of two or more of bromine, chlorine, fluorine, iodine, silicate, carbonate, and sulfate; The molar content of the anion and cation is not more than 10%.
2. The three-site co-doped lithium titanate carbon coating material according to claim 1, characterized in that: The cations are potassium and aluminum, which replace lithium and titanium sites, respectively; And / or the anion is fluorine, replacing the oxygen site.
3. A method for preparing a three-site co-doped lithium titanate carbon coating material, characterized in that: The following steps are involved: The titanium source is dissolved in a solution containing carbon material, a lithium source is added in proportion and mixed evenly, and then a doped potassium source, an aluminum source and a fluorine source are added, and the mixture is heated, stirred, dried, ground and sintered at high temperature in sequence to obtain the product.
4. The method for preparing the three-site co-doped lithium titanate carbon coating material according to claim 3, characterized in that: The titanium source is one or more of tetrabutyl titanate, titanium isopropoxide, and titanium dioxide; and / or the carbon material is selected from one or more of glucose, sucrose, citric acid, tannic acid, and hexadecylamine; and / or the solvent used in the solution of the carbonaceous material is selected from one or more of deionized water, ethanol, n-propanol, isopropanol, ethylene glycol, and propylene glycol; and / or the lithium source is selected from one or more of lithium carbonate, lithium hydroxide monohydrate, lithium nitrate or lithium acetate; and / or the potassium source is selected from one or more of potassium acetate, potassium chloride, potassium sulfate, potassium nitrate, and potassium dihydrogen phosphate; and / or the aluminum source is selected from one or more of aluminum sulfate, aluminum chloride, aluminum nitrate, aluminum acetate, and aluminum carbonate; And / or the fluorine source is selected from one or more of hydrogen fluoride, hydrofluoric acid, fluorspar, sodium fluoride, potassium fluoride, aluminum fluoride, and sulfur hexafluoride.
5. The method for preparing the three-site co-doped lithium titanate carbon coating material according to claim 4, characterized in that: The carbon material is hexadecylamine; and / or the solvent used in the solution of the carbon-containing material is ethanol; and / or the titanium source is tetrabutyl titanate; and / or the lithium source is lithium acetate; and / or the potassium source is potassium acetate; and / or the aluminum source is aluminum acetate; and / or the fluorine source is hydrogen fluoride.
6. The method for preparing the three-site co-doped lithium titanate carbon coating material according to claim 3, characterized in that: Heat and stir in an oil bath at a temperature of 60 to 150°C for 8 to 50 hours; And / or the drying time is 2 to 24 hours; and / or the grinding time is 2 to 120 min; And / or the sintering temperature is 400-800° C., the sintering time is 2-12 hours, and the sintering heating rate is 1-6° C. / min.
7. The method for preparing the three-site co-doped lithium titanate carbon coating material according to claim 6, characterized in that: The oil bath heating temperature is 80°C and the heating time is 24h; And / or the drying time is 24h; And / or the grinding time is 30 min; And / or the sintering temperature is 700° C., the sintering time is 10 h, and the sintering heating rate is 3° C. / min.
8. An electrode comprising the three-site co-doped lithium titanate carbon coating material according to claim 1 or 2, or the three-site co-doped lithium titanate carbon coating material obtained by the preparation method according to any one of claims 3 to 7.
9. Use of the three-site co-doped lithium titanate carbon coating material according to claim 1 or 2, or the electrode according to claim 8 in an organic lithium ion battery.
Citation Information
Patent Citations
Preparation method and use of fluorine-doped lithium titanate lithium ion battery cathode material
CN103346308A
Doped lithium titanium spinel compound and electrode comprising same
CN104081565A
Carbon-clad spinel lithium titanate material, production method and application thereof
CN104253267A
Cited By
Preparation method of lithium ion battery cathode material copper-based lithium titanate with high rate capability
CN120319793A